Cognition in urban-dwelling yellow mongoose, Cynictis penicillata - Muller, Mijke (University of the Witwatersrand, Johannesburg, 2024)
Cognition involves perceiving and processing environmental cues and devising appropriate behavioural responses to act on the acquired information. Studying animal cognition in an urban setting provides insight into the occurrence of behavioural changes in urban-adapted animals. This thesis aimed to investigate the cognitive abilities of a population of yellow mongoose, Cynictis penicillata, inhabiting locations with differing extents of urbanisation in South Africa. First, I investigated whether mongooses could learn to solve a puzzle box problem of increasing complexity. The mongooses were able to solve the problem at each stage of complexity, but took longer in a residential ecological estate than those frequently visiting a residential garden. These results indicated that mongooses were capable of innovation, but their problem-solving abilities were influenced by the level of disturbance in their environment. Secondly, I investigated whether mongooses exhibited cognitive flexibility. The mongooses were able to inhibit a non-rewarding behaviour, even when it was previously rewarded, in favour of a newly rewarded behaviour during the puzzle box task. Additionally, they could solve the puzzle box problem during distraction, but took longer with the most distraction, likely splitting their attention between solving the problem and remaining vigilant. Combined, the mongooses were capable of reversal learning and divided/alternating attention, providing evidence of cognitive flexibility in this mongoose population. Thirdly, I investigated the effects of a direct human approach on the problemsolving ability of mongooses. In areas of heightened human disturbances, the mongooses had reduced tolerance to humans, but were equally efficient at solving the puzzle box problem following human disturbance than those in areas of reduced human disturbance. Those more tolerant of humans improved their problem-solving efficiency, likely adapting to the disturbance. Finally, I investigated whether mongooses experienced a paradox of choice (i.e. whether too much choice can be cognitively challenging). The mongooses in my study appeared to experience cognitive difficulties when presented with extensive choice, providing support for a paradox of choice. These results provide evidence that urban-living yellow mongooses’ successful adaptation to an urban habitat may be attributed to their cognitive abilities, allowing them to exploit novel resources and flexibly adapt to the rapid environmental changes associated with urbanisation. However, the disturbance associated with urbanisation may negatively affect problem-solving efficiency, which may impact successful food acquisition, and the increased availability of resources may be cognitively challenging for urban-living yellow mongooses.
A thesis submitted in partial fulfilment of the requirements for the degree Doctor of Philosophy to the Faculty of Science, School of Animal, Plant and Environmental Sciences, University of the Witwatersrand, Johannesburg, 2023
Keywords: Urban-dwelling; Cynictis penicillata; SDG-15: Life on land; SDG-4: Quality education